Enhanced saccharification levels of corn starch using as a strategy a novel amylolytic complex (AmyHb) from the thermophilic fungus Humicola brevis var. thermoidea in association with commercial enzyme - Marciano, Camila Langer; de Almeida, Aline Pereira; Bezerra, Fabiane Cruz; Giannesi, Giovana Cristina; Cabral, Hamilton; Teixeira de Moraes Polizeli, Maria de Lourdes; Ruller, Roberto [UNESP]; Masui, Douglas Chodi (Springer Nature, 2024)
Amylases represent a versatile group of catalysts that are used for the saccharification of starch because they can hydrolyze the glycosidic bonds of starch molecules to release glucose, maltose, and short-chain oligosaccharides. The amylolytic complex of the thermophilic filamentous fungus Humicola brevis var. thermoidea (AmyHb) was produced, biochemically characterized, and compared with the commercial amylase Termamyl. In addition, the biotechnological application of AmyHb in starch saccharification was investigated. The highest production was achieved using a wheat bran medium at 50 °C for 5–6 days in solid-state fermentation (849.6 ± 18.2 U·g−1) without the addition of inducers. Optimum amylolytic activity occurred at pH 5.0 at 60 °C, and stability was maintained between pH 5.0 and 6.0, with thermal stability at 50–60 °C, especially in the presence of Ca2+. These results were superior to those found with Termamyl. Both enzymes were strongly inhibited by Hg2+, Cu2+, and Ag+; however, AmyHb displayed increased activity in the presence of Mn2+ and Na+. In addition, AmyHb showed greater tolerance to a wide range of ethanol concentrations. AmyHb appears to be a complex consisting of glucoamylase and α-amylase, based on its substrate specificity and TLC. The hydrolysis tests on cornstarch flour showed that the cocktail of AmyHb50% + Termamyl50% significantly increased the release of glucose and total reducing sugars (36.6%) when compared to the enzymes alone. AmyHb exhibited promising physicochemical properties and good performance with commercial amylase; therefore, this complex is a biotechnological alternative candidate for the bioprocessing of starch sources.
Keywords: Amylase; Cornstarch hydrolysis; Humicola brevis; Solid state fermentation; Thermophilic fungi